Hubungan Jarak Kelahiran Dan Jumlah Anak Dengan Status Gizi Balita Usia 6 – 59 Bulan - Awani, Andi Tenri; Wahyuni, Fitri; Yusuf, Kurnia; Masithah, St. Masithah; Rahmaniar, Andi Rahmaniar (Lembaga Penelitian dan Pengabdian Masyarakat Politeknik Muhammadiyah Makassar, 2025)
Nutritional status is a state of the body due to food intake and use of nutrients. Nutritional problems are influenced by many factors that influence each other in a complex manner. The purpose of this study was to determine the relationship between pregnancy spacing and the number of children with the nutritional status of toddlers. The design used in this study was descriptive correlation with a cross-sectional method with a random sampling technique and 30 samples were obtained from 398 populations. The analysis was carried out using the chi-square test. Based on the results of the chi-square test, the p value <0.004 was shown for the number of children variable and p <0.017 for the birth spacing variable with the nutritional status of toddlers, so it can be concluded that there is a relationship between pregnancy spacing and the number of children with the nutritional status of toddlers. Therefore, the advice that can be given to the community is to urge mothers to be aware of the importance of their baby's nutritional status and what factors influence nutritional status. This education can be done through health education programs, nutritional monitoring, and access to adequate maternal and child health services.